Cover Image. (26th September 2017) - Vescarelli, Enrica; Pilloni, Andrea; Dominici, Francesco; Pontecorvi, Paola; Angeloni, Antonio; Polimeni, Antonella; Ceccarelli, Simona; Marchese, Cinzia
Abstract : The cover image, by Enrica Vescarelli et al., is based on the In Vitro Research Autophagy activation is required for myofibroblast differentiation during healing of oral mucosa, DOI:10.1111/jcpe.12767 .